Tuning the surface coating of IONs toward efficient sonochemical tethering and sustained liberation of topoisomerase II poisons - Michalkova, Hana; Strmiska, Vladislav; Kudr, Jiri; Skubalova, Zuzana; Tesarova, Barbora; Svec, Pavel; Richtera, Lukas; Zitka, Ondrej; Adam, Vojtech; Heger, Zbynek (International journal of nanomedicine, 2019)
BACKGROUND: Iron oxide nanoparticles (IONs) have been increasingly utilized in a wide spectrum of biomedical applications. Surface coatings of IONs can bestow a number of exceptional properties, including enhanced stability of IONs, increased loading of drugs or their controlled release. METHODS: Using two-step sonochemical protocol, IONs were surface-coated with polyoxyethylene stearate, polyvinylpyrrolidone or chitosan for a loading of two distinct topo II poisons (doxorubicin and ellipticine). The cytotoxic behavior was tested in vitro against breast cancer (MDA-MB-231) and healthy epithelial cells (HEK-293 and HBL-100). In addition, biocompatibility studies (hemotoxicity, protein corona formation, binding of third complement component) were performed. RESULTS: Notably, despite surface-coated IONs exhibited only negligible cytotoxicity, upon tethering with topo II poisons, synergistic or additional enhancement of cytotoxicity was found in MDA-MB-231 cells. Pronounced anti-migratory activity, DNA fragmentation, decrease in expression of procaspase-3 and enhancement of p53 expression were further identified upon exposure to surface-coated IONs with tethered doxorubicin and ellipticine. Moreover, surface-coated IONs nanoformulations of topo II poisons exhibited exceptional stability in human plasma with no protein corona and complement 3 binding, and only a mild induction of hemolysis in human red blood cells. CONCLUSION: The results imply a high potential of an efficient ultrasound-mediated surface functionalization of IONs as delivery vehicles to improve therapeutic efficiency of topo II poisons.
Keywords: nanoparticles; železité sloučeniny; doxorubicin; povrchové vlastnosti; DNA-topoisomerasy typu II; Cell Line; Male; Ferric Compounds; iron oxide; Nanoparticles; nanočástice; release kinetics; Sonication; Static Electricity; inhibitory topoisomerasy II; Cell Death; DNA Topoisomerases, Type II; buněčná smrt; mužské pohlaví; ellipticine; Cell Movement; biokompatibilní potahované materiály; kinetika; Coated Materials, Biocompatible; lidé; Wound Healing; Humans; statická elektřina; Surface Properties; pohyb buněk; Drug Liberation; vibrace ultrazvukové; buněčné linie; uvolňování léčiv; Topoisomerase II Inhibitors; Kinetics; Doxorubicin; hojení ran